2016
DOI: 10.13005/ojc/320203
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of A Stability-Indicating Liquid Chromatographic Method for Determination of Valsartan and Hydrochlorthiazide Using Quality by Design

Abstract: The present paper involves the analytical quality by design (AQbD)-based development of a simple, rapid, accurate and precise stability-indicating method for the estimation of valsartan and hydrochlorothiazide. Optimized mobile phase (v/v/v) was water (containing 0.25 ml/L triethylamine), methanol and acetonitrile (50:38:37, pH adjusted to 3.0±0.1). Chromatographic separation was achieved on Hypersil ® -Gold C 18 (150 x 4.6 mm, 5 µm, Thermo Fisher Scientific, USA), column at 25 ± 2 °C. The method was validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…According to the cited works, the highest degradation of hydrochlorothiazide occurred in methanol (53.56%) [ 25 ], 1 M NaOH (69.60%) and 1 M HCl (81.70%) [ 21 ]. In other works, degradation in acidic medium ranged from 0.4 to 17.86% while in alkaline medium from 0.15 to 36.82% [ 19 , 20 , 22 , 25 , 28 , 30 – 32 ]. Hydrochlorothiazide was shown to be stable in the buffer of pH 2.0 and less stable at pH 9.0, where 9.07% of the drug degraded [ 23 ].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…According to the cited works, the highest degradation of hydrochlorothiazide occurred in methanol (53.56%) [ 25 ], 1 M NaOH (69.60%) and 1 M HCl (81.70%) [ 21 ]. In other works, degradation in acidic medium ranged from 0.4 to 17.86% while in alkaline medium from 0.15 to 36.82% [ 19 , 20 , 22 , 25 , 28 , 30 – 32 ]. Hydrochlorothiazide was shown to be stable in the buffer of pH 2.0 and less stable at pH 9.0, where 9.07% of the drug degraded [ 23 ].…”
Section: Resultsmentioning
confidence: 90%
“…They were carried out in a solid state [ 20 , 22 , 24 , 28 , 31 ] and less frequently in solutions [ 25 , 29 , 30 ]. Stability of hydrochlorothiazide was studied in 1M HCl [ 19 – 22 , 25 , 30 – 32 ], 5 M HCl [ 28 ], 1 M NaOH [ 19 – 22 , 25 , 27 , 31 – 37 ], 5 M NaOH [ 28 ], buffers [ 23 ] and methanol [ 19 , 25 ]. One study on degradation of hydrochlorothiazide by LC/MS method was reported in the literature [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have used the design of experiments to run a few trials and obtain the optimum conditions to develop the method, validate the same for the drug bilastine in its pure and dosage form using high performance liquid chromatography. Many papers have published the use of such software's [1][2][3][4] . The method development and validation of the drug methotrexate using high performance liquid chromatography (HPLC) was established with the aid of design of experiments 5 .…”
Section: Preparation Of Mobile Phasementioning
confidence: 99%